Mother-Tongue: A way to Optimize Quality Education - Dr Sanjeev Tomar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
All over the world, there has been a burning issue of debate over the need for students to have their own mother tongue as a medium of instruction since many decades. Our educationists also support the mother tongue as a medium of instruction to boost up child’s imagination power and learning capacities, and also to diminish the inequalities. While on the other hand, Anglicists had been in support of modern western education to Indian children in English medium. The people who were in favour of Anglicists are Thomas Babington, Macaulay, James’s mill etc. This paper highlights the upon the burning issue that medium of instruction at the school level should be – English or Mother tongue for providing the quality education to diminish inequalities and boost up creativity among children.